FACTORS INFLUENCING PURCHASE INTENTION OF LOCAL INDONESIAN FASHION BRANDS IN THE DIGITAL ERA - Sander, Ongky Alex (LPPM Universitas Malikussaleh, 2025)
The rise of local fashion brands in Indonesia has shown significant growth, with many now competing on an international scale. However, challenges such as fierce competition, limited brand awareness, and inadequate promotional strategies still hinder the industry. This study explores the influence of Country of Origin, Brand Consciousness, and Brand Awareness on Purchase Intention toward local fashion products in Indonesia. Using a quantitative approach with structural equation modeling (PLS-SEM) and data from 257 Indonesian millennial and Gen Z respondents. The research finds that all three factors significantly affect purchase intention. Brand-conscious consumers are more likely to purchase products that reflect their social status, while higher brand awareness boosts consumer trust and confidence. Additionally, the perception of the product's origin, particularly the